Stress-Strain Behavior of Steel Fiber-Reinforced Concrete Cylinders Spirally Confined with Steel Bars - Bambang Sabariman; Agoes Soehardjono; Wisnumurti Wisnumurti; Ari Wibowo; Tavio Tavio (Advances in Civil Engineering)
The compressive strength of concrete according to certain codes can be based on the compressive strength of unconfined plain standard concrete cylinders tests at the age of 28 days. In this paper, the standard concrete cylinders were spirally confined with steel bars and with/without hooked-end steel fibers. The influence of the use of hooked-end steel fiber in spirally confined concrete with various pitches was investigated. It can be seen that the use of hooked-end steel fiber contributes significantly in improving both compressive strength and ductility of concrete. The compressive strength and ductility of steel fibered concrete also increase with the reduction of the spiral’s pitch.